Drug Abuse an Intoxicated Web Around Youth. Case Studies of Abusers of Jammu - Sharma., Priyanka (International Journal of Psychosocial Rehabilitation, 2014)
Drug abuse is a menace that is spreading among youth at an alarming rate. The vicious cycle of abuse is a life-threatening experience, which needs to be broken at any cost. The present paper is an analysis of case studies of three abusers undergoing treatment in the drug addiction center. The peep into the cases gives an understanding of the precipitating/ triggering factors pushing youth towards drug usage. The case studies also indicate personality profiles which are more prone to abuse. In addition, stressors and stimulators in life pushing youth towards abuse are also analyzed. Introspection by the abusers and family members indicates possible preventive plans for the vulnerable groups and for other significant people around them